The Role of Vitamin C in the Prevention of Premature Rupture of Membranes - Tiara Cornela Azqinar; Agung Ikhssani (Journal of Maternal and Child Health Sciences (JMCHS), 2021)
Premature rupture of membranes [PROM] is an early event in approximately one third of preterm births resulting in significant infant mortality and morbidity. The exact mechanism by which the fetal membranes weaken and rupture in term and preterm pregnancy is unknown. However, it has been hypothesized that the fetal membranes weaken and eventually rupture as a result of collagen remodeling and apoptosis. Some studies have speculated that vitamin C supplementation during pregnancy will be useful in the prevention of PROM but some studies have also shown that vitamin C supplementation does not affect normal fetal membrane remodeling processes leading to weakening and rupture of the fetal membranes. This literature review discusses the role of Vitamin C in the prevention of PROM, where the role of vitamin C can induce collagen degradation and apoptosis. The assumption that vitamin C supplementation may be a prophylactic regimen for premature PROM should be investigated further. Caution should be exercised in using vitamin C supplements to prevent PROM in pregnant women. This literature review discusses the role of vitamin C in preventing premature rupture of membranes.